A Method to Obtain Gas-PDMS Membrane Interaction Parameters for UNIQUAC Model - 林东杰 丁忠伟 刘丽英 马润宇 (Chinese journal of chemical engineering, 2013)
The recovery or capture of one or more components from gas mixture by membrane separation has become a research focus in recent years.This study investigates the gas-membrane solution equilibrium,for which Henry’s law is not applicable if the gas phase is a mixture.This problem can be solved by using UNIQUAC model to calculate the activity coefficient of gas dissolved in the membrane.A method was proposed in this study to obtain the gas-membrane interaction parameter for UNIQUAC model.By the experiments of gas permeation through polydimethylsiloxane PDMS membrane,the solubility coefficients of some gases（N2,CO2,CH4） were measured.Through non-linear fitting UNIQUAC model to the experimental results from this study and in literature（H2,O2,C3H8）,the gas-membrane interaction parameters for these gases were obtained.Based on these parameters,the activity coefficients of the dissolved gas were calculated by UNIQUAC model,and their values agree well with the experimental data.These results confirm the feasibility and effectiveness of the proposed method,which makes it possible to better predict gas-membrane solution equilibrium.